An Upper Bound in a Law of the Iterated Logarithm for Rademacher Function (The Nepali Mathematical Sciences Report, 2022)
N. Kolmogorov introduced a law of the iterated logarithm, abbreviated LIL, in the case of independent random variables. Over the years, an analog of his result has been introduced in various contexts of analysis. Here, we introduce a similar LIL in the context of sums of Rademacher functions.